Investigating The Antecedents of Consumer Brand Engagement to Luxury Brands on Social Media - Angga Febrian; Larasati Ahluwalia (School of Business, IPB University (SB-IPB), 2021)
The purpose of this study is to analyze the antecedent consumer involvement and brand self expressiveness and brand community identification of the three dimensions of consumer brand engagement (CBE) (cognitive, emotional, behavior) in the luxury brand on social media. The data was collected through an online questionnaire which was filled in by 125 respondents who have experience in buying luxury brands using purposive sampling. The empirical study was conducted using structural equation modeling SmartPls. The results of the study stated that Consumer Involvement has a negative impact, brand self expressiveness and consumer brand identification have a positive impact on dimensions of CBE. Tests were also conducted to see the consequences of CBE, namely an increase in brand image and brand loyalty. Managers of luxury brand companies must increase CBE by utilizing and managing consumers following social media and creating communities to make it easier for consumers to get to know the advantages of luxury brand products. This study is a pioneer, as it extends the consumer engagement model to the social media context luxury brand by adding brand community identification as an antecedent CBE. Keywords: consumer brand engagement, brand image, brand loyalty, luxury brand, social media